Examining access to Psychoeducational Assessments by Socioeconomic factors for children with behavioral referrals. (18th May 2018) - Gander, Sarah; Campbell, Sarah
Abstract: BACKGROUND: The psycho-educational assessment (PEA) is often recommended in behavioural presentations in children. The PEA assesses cognitive ability and detects any learning disabilities which may be the direct cause, or comorbidity, of a behavioral problem. This essential tool directs the child and family to appropriate treatment or intervention, and is critical for the school to design effective programming for the child. However, access to this assessment is quite variable. Some students may receive the PEA from a school psychologist if it has been established that other interventions have proven ineffective, but may experience long wait times. This study looked at a group of behavioural referrals at a local paediatric clinic to determine how many children had received a PEA, and if access seemed to be affected by their socioeconomic status (SES). OBJECTIVES: To identify how many of these behavioural referrals have also received PEAs. To understand the SES distribution among the children receiving behavioural referrals. To determine if children with higher SES status are more likely to have received PEAs. DESIGN/METHODS: All behavioural referrals at this clinic are subject to an intake interview with a clinic nurse, who gathers a detailed medical, social and family history. This includes a list of previously accessed services and resources, including the PEA. Socioeconomic status was defined by the Quintile-Annual-Income-Per-Person-Equivalent (QAIPPE) associated with the dissemination area (DA) of the family residence. Patients were divided into these quintiles to determine the number of referrals from each quintile, and the percentage of children from each quintile that had received a PEA. RESULTS: More than half of the referrals (51.2%; n=342) come from families living in DAs of the two lowest income quintiles. Of those children living in neighbourhoods in the two highest income quintiles, 27% had received the PEA prior to referral, as compared to 12.6% of those children living in the three lower income quintile neighbourhoods. CONCLUSION: This demonstrates that children from low income neighbourhoods are receiving more behavioural referrals but are less likely to have received a PEA. This is a barrier to delivering timely and effective service as many children will wait over a year for their paediatric appointment only to find that they may have been better serviced elsewhere. Improving access to the PEA would improve the treatment of this population and help eliminate duplication and unnecessary service provision.